Organización contable a la empresa “Distribuciones Licogaseosas” de la parroquia Cumbaratza del cantón Zamora. Período del 01 de abril al 30 de junio del 2022. - Sizalima Herrera, Jana Gissella (2023)
This present research project entitled ACCOUNTING ORGANIZATION IN THE COMPANY "DISTRIBUCIONES LICOGASEOSAS" OF THE PARROQUIA CUMBARATZA OF THE CANTON ZAMORA. PERIOD FROM APRIL 1 TO JUNE 30, 2022, was done as a prior requirement to obtain the college degree of Engineer in Accounting and Auditing in accordance with the provisions of the Academic Regulations of the National University of Loja and to provide a significant and timely contribution to the owner on the economic and financial situation of the distributor, serving as a basis for the correct and accurate decision making for the benefit of control, management and improvement of the entity. For the purpose of complying with the objectives of this degree work, an orderly chart of accounts was done, classified and codified based on the company's economic activity, needs, and nature. Each account has its own manual that describes, elaborates, and specifies its function, debits, credits, and balances for assets, liabilities, equity, income, costs, and expenses. Consequently, an initial inventory was done, through the physical verification of the merchandise stock and documents that support the rights and obligations with which the company starts the fiscal year under study, obtaining a total of assets of $ 130,739.35; liabilities of $ 598.00 and equity of $ 130,141.35, in order to continue with the preparation of the Statement of Initial Situation. With the orderly selection of the source documentation, an accounting process was developed, along with the preparation of auxiliary records of purchase and sale of merchandise that allow to detail in an analytical and systematic way the transactions generated daily, auxiliary of accounts receivable that show the detail of the sales on credit, auxiliary of accounts payable that allows to break down the movement of credits and debits to suppliers, payment roles and depreciation tables that serve as support in the operations carried out; The memorandum of operations was then structured, thus allowing the chronological and systematic registration of the economic facts in the daily book applying the permanent account system, consecutively this information was consolidated in the general ledgers and its balances in the trial balance; the worksheet together with the adjustments, allowed the presentation of the financial statements that summarize the economic and financial activity of the distributor, thus obtaining a total of assets of $ 125. 533.45; liabilities of $ 1,963.25; equity of $ 123,570.20; income of $ 7,662.72; expenses of $ 14,233.87, and as a result a net loss of $ 6,571.15.